DRG2 levels in prostate cancer cell lines predict response to PARP inhibitor during docetaxel treatment - Jeong Min Lee; Won Hyeok Lee; Seung Hyeon Cho; Jeong Woo Park; Hyuk Nam Kwon; Ji Hye Kim; Sang Hun Lee; Ji Hyung Yoon; Sungchan Park; Seong Cheol Kim (Investigative and Clinical Urology)
"Purpose: Developmentally regulated GTP-binding protein 2 (DRG2) regulates microtubule dynamics and G2/M arrest during docetaxel treatment. Poly ADP-ribose polymerase (PARP) acts as an important repair system for DNA damage caused by docetaxel treatment. This study investigated whether DRG2 expression affects response to PARP inhibitors (olaparib) using prostate cancer cell lines PC3, DU145, LNCaP-FGC, and LNCaP-LN3. Materials and Methods: The cell viability and DRG2 expression levels were assessed using colorimetric-based cell viability assay and western blot. Cells were transfected with DRG2 siRNA, and pcDNA6/V5-DRG2 was used to overexpress DRG2. Flow cytometry was applied for cell cycle assay and apoptosis analysis using the Annexing V cell death assay. Results: The expression of DRG2 was highest in LNCaP-LN3 and lowest in DU145 cells. Expressions of p53 in PC3, DU145, and the two LNCaP cell lines were null-type, high-expression, and medium-expression, respectively. In PC3 (DRG2 high, p53 null) cells, docetaxel increased G2/M arrest without apoptosis; however, subsequent treatment with olaparib promoted apoptosis. In DU145 and LNCaP-FGC (DRG2 low), docetaxel increased sub-G1 but not G2/M arrest and induced apoptosis, whereas olaparib had no additional effect. In LNCaP-LN3 (DRG2 high, p53 wild-type), docetaxel increased sub-G1 and G2/M arrest, furthermore olaparib enhanced cell death. Docetaxel and olaparib combination treatment had a slight effect on DRG2 knockdown PC3, but increased apoptosis in DRG2-overexpressed DU145 cells. Conclusions: DRG2 and p53 expressions play an important role in prostate cancer cell lines treated with docetaxel, and DRG2 levels can predict the response to PARP inhibitors."